Consumer’s behavior towards credit card usage in Kota Bharu / Syarah Raidah Shazula - Shazula, Syarah Raidah (2012)
Nowadays, the credit card ownership has spread widely among people. The spread of credit card usage has results the increase number of debts in the developing nation. This study has carried out in order to examine the factors that influence the credit cards usage especially among people in Kota Bharu. Besides that, the researchers also want to measure the attribute towards the lifestyle of consumers on the credit cards usage. Thus, the researcher also had looked for the factors that influence the usage of credit card among consumers and focus on the specific areas. By using the specific research method, the researcher has collected and gathered the information on the factors that influence the usage of credit card as well as the pattern of credit card user’s behavior usage. Moreover, the researcher also needs to know the main factor that contributes to the credit card usage in Kota Bharu. There are 120 questionnaires were distributed in Kota Bharu, Kelantan in order to collect the data